2011
DOI: 10.1159/000323797
|View full text |Cite
|
Sign up to set email alerts
|

Role of Familial, Environmental and Occupational Factors in the Development of Parkinson’s Disease

Abstract: Background: Despite intensive research during the past several decades, the cause of Parkinson’s disease remains unknown. Infections, toxins, lifestyle and hereditary factors have all been supposed to play a role in the genesis of Parkinson’s disease. The final mechanisms of neuronal injury and death are probably similar, where both genetic and environmental factors are important, and these two factors interact along the etiopathogenic pathway. Objective: The purpose of the present study is to evaluate the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 42 publications
0
14
1
2
Order By: Relevance
“…Between-study variance of RRs was lowest for fungicide use, independent of study classification, and greatest for insecticide use, rural living and paraquat use ( Table 4 ). For insecticide use, the Tier 2 study by Das et al [ 58 ] was an “outlier” study that contributed the most to the Tier 2 between-study heterogeneity; removal of this study resulted in a 49 percent reduction in τ 2 from 0.57 to 0.29. As another example, the Tier 2 study by Liou et al [ 59 ] contributed the most to the Tier 2 between-study variability for paraquat; when this study was removed, τ 2 was reduced almost 10-fold, from 0.24 to 0.03.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Between-study variance of RRs was lowest for fungicide use, independent of study classification, and greatest for insecticide use, rural living and paraquat use ( Table 4 ). For insecticide use, the Tier 2 study by Das et al [ 58 ] was an “outlier” study that contributed the most to the Tier 2 between-study heterogeneity; removal of this study resulted in a 49 percent reduction in τ 2 from 0.57 to 0.29. As another example, the Tier 2 study by Liou et al [ 59 ] contributed the most to the Tier 2 between-study variability for paraquat; when this study was removed, τ 2 was reduced almost 10-fold, from 0.24 to 0.03.…”
Section: Resultsmentioning
confidence: 99%
“…RR = relative risk, LCL = lower limit of the 95% confidence interval, UCL = upper limit of the 95% confidence interval. Citations for studies appearing in this figure can be found here: [ 55 , 58 , 80 , 81 , 92 , 102 , 104 , 114 , 115 , 119 , 121 , 122 , 132 , 135 , 137 , 143 , 155 158 ].…”
Section: Resultsmentioning
confidence: 99%
“…) . Twelve articles were excluded because they either did not contain data on head injury or did not provide adequate definitions of head injury or adequate diagnostic criteria for PD . Twenty‐two studies (19 case–control studies, 2 nested case–control studies, and 1 cohort study) were included in both the systematic review and the meta‐analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another 46 relevant publications [3,9,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98] not fulfilling good scientific standards regarding the exposures under study are summarized in Table 2.…”
Section: Methodsmentioning
confidence: 99%